Draft Annual Plan 1971-72 Jammu & Kashmir - Planning Commission (Planning Commission, 1971)
Jammu and Kashmir is the northern most State in the country and is bordered by 2 hostile neighbors who have in recent years, subjected the State to aggression on two occasions. The area of the State on the Indian side of the ceasefire line is 0.54 million sq. miles. The State has an estimated population of about 45 lakhs at present. Although the State is generally hilly, it is possible to identify it into three distinct geo-physical regions. The Jammu region of the State is flanked by Punjab, Himachal Pradesh and Pakistan. Only a strip of the region bordering Punjab is flat and the rest of the region is hibly the terrain rising gradually to a height of about 12,000 feet on the Pir Panjal range. The region contains 3 rivers basins, that of the Chenab the Ravi and the Tawi. The Chenab basin has considerable potential for hydel power generation, while the Ravi and the Tawi basins- have a high irrigation potential.
Government of Jammu and Kashmir
Government of India Planning Commission
Keywords: Creating the economic in restructure for development; Achieving national targets for family planning; Economic Background; Financial Resources; development of commercial crops; forest and soil conservation; cooperative movement in the State; irrigation and flood control; drainage and dewatering Programme; Industry and mining; Department of Information and Publicity.